The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1038/ng1067
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an epigenetic mechanism by which Hsp90 acts as a capacitor for morphological evolution

Abstract: Morphological alterations have been shown to occur in Drosophila melanogaster when function of Hsp90 (heat shock 90-kDa protein 1alpha, encoded by Hsp83) is compromised during development. Genetic selection maintains the altered phenotypes in subsequent generations. Recent experiments have shown, however, that phenotypic variation still occurs in nearly isogenic recombinant inbred strains of Arabidopsis thaliana. Using a sensitized isogenic D. melanogaster strain, iso-Kr(If-1), we confirm this finding and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
328
0
8

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(345 citation statements)
references
References 19 publications
9
328
0
8
Order By: Relevance
“…Similar to studies from Lindquist's lab [11], it was recently reported that impairment of Hsp90 activity in flies either by genetic mutation or pharmacological inhibition resulted in inheritance of a specific eye phenotype in an isogenic fly line [13]. However, in contrast, an epigenetic basis for capacitor function of Hsp90 was revealed by the finding that depletion of Hsp90 induced an altered …”
Section: Interplay Between Genetics and Epigeneticssupporting
confidence: 53%
See 3 more Smart Citations
“…Similar to studies from Lindquist's lab [11], it was recently reported that impairment of Hsp90 activity in flies either by genetic mutation or pharmacological inhibition resulted in inheritance of a specific eye phenotype in an isogenic fly line [13]. However, in contrast, an epigenetic basis for capacitor function of Hsp90 was revealed by the finding that depletion of Hsp90 induced an altered …”
Section: Interplay Between Genetics and Epigeneticssupporting
confidence: 53%
“…Although there is clear evidence that phenotypes induced by Hsp90 inhibition are heritable and can be fixed by phenotypic selection [11][12][13], the exact mechanism of the inheritance process remains unclear. Several lines of evidence suggest that phenotypic variations induced by Hsp90 inhibition become independent of the chaperone after they are inherited across successive generations.…”
Section: Inheritance Of Phenotypes Induced By Hsp90 Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 The effect of GA on Caspase 8 expression in neuroblastoma has not been reported, but work in Drosophila has shown that compromise of Hsp90 function can alter gene expression through effects on chromatin remodeling factors. 35 In future work, it will be interesting to see whether GA exposure restores Caspase 8 expression in neuroblastoma cells, thus contributing to the induction of apoptotic death in this tumor type.…”
Section: Discussionmentioning
confidence: 99%